2012
DOI: 10.1136/bcr-2012-006259
|View full text |Cite
|
Sign up to set email alerts
|

Digital gangrene as the initial presentation of systemic lupus erythematosus

Abstract: SummarySystemic lupus erythematosus (SLE) has rarely been reported among African blacks. However, recent reports may indicate otherwise. Digital gangrene in lupus patients has been reported in different populations and has mostly been seen in patients with long-standing lupus. Digital gangrene as the initial presentation of SLE has rarely been reported, even among African blacks. Two cases of digital gangrene as the initial presentation in Nigerian lupus patients are hereby presented. The medical and surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…Vascular injury is an important characteristic of SLE. Digital gangrene in SLE is a rare form of vascular injury and considered to be a severe complication of SLE that generally leads to digital amputation (1,2). The mechanisms include vasculitis, premature atherosclerosis, vasospasm, and hypercoagulability related to antiphospholipid antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular injury is an important characteristic of SLE. Digital gangrene in SLE is a rare form of vascular injury and considered to be a severe complication of SLE that generally leads to digital amputation (1,2). The mechanisms include vasculitis, premature atherosclerosis, vasospasm, and hypercoagulability related to antiphospholipid antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Complications of lupus have also been reported such as lupus nephritis [32,33] and neuropsychiatric lupus [34]. Rare complications have also been reported such as an associated digital gangrene [35]. Juvenile SLE has also been reported in 14 black patients out of 36 cases of lupus nephritis from a study in South Africa [36].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 88%
“…8 However, some cases of digital gangrene as a primary event in SLE have been reported. 3,6,[9][10][11] The majority of cases reported in the literature have proved that digital gangrene occurs in young SLE patients and that the occurrence of this complication in older adult patients is extremely rare. 2,6,9,10 To the best of the authors' knowledge, only three cases of digital gangrene have been reported in patients with SLE at an older age (after 50 years old).…”
Section: Discussionmentioning
confidence: 99%
“…It is the initial manifestation of the disease in only 0.2% of cases. 2,3 It was initially identified by Dubois 4 and Alarcon-Segovia. 5 Mechanisms, such as vasculitis, thromboembolism, premature atherosclerosis, vasospasm, and coagulability can contribute to the development of gangrene.…”
Section: Introductionmentioning
confidence: 99%